2015
DOI: 10.1007/s00330-014-3586-y
|View full text |Cite
|
Sign up to set email alerts
|

Normal sonoanatomy of the paediatric entheses including echostructure and vascularisation changes during growth

Abstract: • The tendons of children exhibit the same fibrillar structure as adults • Tendon thickness at enthesis insertion in children is not influenced by gender • Cartilage thickness in children decreases with advancing age and varies with gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
1
15
3
Order By: Relevance
“…NSAID use was associated with an increased risk of synovial effusion and increased synovial effusion/hypertrophy quantitative score. In previous reports of knee tendon features on MSUS in healthy children, no vascularity was detected in the patellar tendons [25,26]. Patellar tendon hyperemia is a significantly different finding in our case participants compared to control groups, which suggests that the tendon may be associated with pathology in hypermobile joints.…”
Section: Discussioncontrasting
confidence: 70%
“…NSAID use was associated with an increased risk of synovial effusion and increased synovial effusion/hypertrophy quantitative score. In previous reports of knee tendon features on MSUS in healthy children, no vascularity was detected in the patellar tendons [25,26]. Patellar tendon hyperemia is a significantly different finding in our case participants compared to control groups, which suggests that the tendon may be associated with pathology in hypermobile joints.…”
Section: Discussioncontrasting
confidence: 70%
“…Furthermore it remains normal US enthesis in children to be defined. Jousse-Joulin et al found that tendon thickness at enthesis insertion in children varied significantly with age, but was not influenced by gender [25].Also, the aspect of the bone-cartilage interface varied according to whether the ossification centre had deve loped within the cartilage: wavy in younger patients, then rounded and, finally, hyperechoic at puberty [25]. Important to say is that enthesalgia may be present in up to 1/3 of healthy school-age children [20,26].…”
Section: Us Appearance Of Musculoskeletal Structures In Healthy Childrenmentioning
confidence: 99%
“…Sonographic appearances of normal joints and entheses in healthy children and changes that occur with age are documented in recent articles. 12,13 Apophyseal avulsion injuries Acute apophyseal injury often occurs during sporting activity when a sudden forceful muscular contraction applies violent traction tension to the tendon attachment at the apophysis. The apophysis can partially or completely detach from the underlying bone, occasionally with complete functional loss of the attaching muscle.…”
Section: Normal Paediatric Skeletal Anatomymentioning
confidence: 99%
“…Sonographic appearances of normal joints and entheses in healthy children and changes that occur with age are documented in recent articles. 12,13…”
Section: Normal Paediatric Skeletal Anatomymentioning
confidence: 99%